Neurotoxicity of aluminium chloride and okadaic acid in zebrafish: Unravelling Alzheimer's disease model via learning and memory function evaluation - S.Z. Raduan; Q.U. Ahmed; M.R.A. Rusmili; A.S.M. Sabere; M.S. Haris; M.F. Shaikh; W.A.W. Sulaiman; M.H. Mahmood (Neurology Perspectives)
Introduction/objectives: Alzheimer's disease (AD) is characterised by a progressive decline in cognitive abilities, especially learning and memory. To validate the zebrafish as a suitable model organism for AD, the study examined the effects of 2 neurotoxin agents, aluminium chloride (AlCl3) and okadaic acid (OKA). In the full experimental design, both neurotoxins were administered intraperitoneally at 3 distinct doses (low, medium, and high) twice weekly for 21 days. At 3 time-points, behavioural tasks were conducted on day 7 (short duration), day 14 (moderate duration), and day 21 (long duration). The behavioural tasks consisted of a novel tank test lasting 6 min, followed by a T-maze tank test lasting 5 min. Methods: In this article, the T-maze tank test was discussed in detail to evaluate which neurotoxins and their optimal dosages are impactful in developing a zebrafish AD model towards learning and memory functions. This evaluation measured four parameters: the amount of time spent in the wrong arm, the total distance travelled in the deeper chamber, and the 3-h and 24-h inflexion ratios. Results: In summary, a 100 nM dosage of OKA with a maximum of 21 days of evaluation resulted in significant (P<.05) outcomes in all parameters evaluated. The longest duration was spent in the wrong arm, accompanied by a reduction in the total distance travelled in the deeper chamber and a decreasing pattern in the 3-h and 24-h inflexion ratios. Conclusion: These observations suggest that OKA is the optimal choice of neurotoxin for a validated and optimised zebrafish AD model. Resumen: Introducción/objetivos: Enfermedad de Alzheimer (EA) se caracteriza por un deterioro progresivo de las capacidades cognitivas, especialmente en el aprendizaje y la memoria. Para validar el pez cebra como un organismo modelo adecuado para la EA, el estudio examinó los efectos de dos agentes neurotóxicos, el cloruro de aluminio (AlCl3) y el ácido okadáico (OKA). En el diseño experimental completo, ambos neurotóxicos se administraron por vía intraperitoneal en tres dosis distintas (baja, media y alta) dos veces por semana durante 21 días. En tres momentos diferentes, se llevaron a cabo tareas de comportamiento en el día 7 (duración corta), día 14 (duración moderada) y día 21 (duración larga). Las tareas de comportamiento consistieron en una prueba de tanque novedoso de seis minutos, seguida de una prueba de tanque en forma de T que duró cinco minutos. Métodos: En este artículo, se discutió en detalle la prueba de tanque en forma de T para evaluar qué neurotóxicos y sus dosis óptimas son impactantes en el desarrollo de un modelo de EA en pez cebra hacia las funciones de aprendizaje y memoria. Esta evaluación midió cuatro parámetros: el tiempo pasado en el brazo incorrecto, la distancia total recorrida en la cámara más profunda y las relaciones de inflexión a las 3 horas y 24 horas. Resultados: En resumen, una dosis de 100 nM de OKA con un máximo de 21 días de evaluación resultó en resultados significativos (p < 0.05) en todos los parámetros evaluados. Se pasó la mayor duración en el brazo incorrecto, acompañada de una reducción en la distancia total recorrida en la cámara más profunda y un patrón decreciente en las relaciones de inflexión a las 3 horas y 24 horas. Conclusión: Estas observaciones sugieren que el OKA es la elección óptima de neurotóxico para un modelo de EA validado y optimizado en pez cebra.